IbM PENGEMBANGAN UKM BATIK KECAMATAN SUMPIUH KABUPATEN BANYUMAS - Lestari, Sri (Performance, 2014)
Development of small and medium businesses batik in subdistrict Sumpiuh,Banyumas was conducted on small and medium businesses batik Budi Djamil and BatikTata. The purpose of this activity is to provide the support equipment production andassistance to make proposals for manufacturing production equipment toDisperindagkop, Banyumas. To give counseling, training and mentoring financialmanagement, bookkeeping activities, provide education and training on the use offinancial reporting based computer information systems, especially for small andmedium businesses Batik Tata. It also give guidance about management production anddevelopment of design, conduct design of manufacture packaging and label design toincrease the sale value and customer value, and also it will bring assistance onmanagement marketing and e-marketing. Method with extension activities, training,coaching and mentoring can bring benefits that can increase the production capacity ofpartners, increasing sales turnover and overcome the problems of the partners.